Problematizing ‘pro-feminist’ depictions of female on male rape: American Horror Story’s ‘Rape of the Monsignor’ - Cohen, Claire (Crime, media, culture, 2020)
Dramatized depictions of female on male rape, in inverting the conventional gendered rape binary of male assailant/female victim, are commonly regarded as subverting gender norms, and are thus celebrated as pro-feminist. I present a Foucauldian problematization of this rationale ? arguing that, through a process of over-writing gender, inversion of the norm masks a ?reversion to the norm?. To interpret this as pro-feminist, one must be distracted by corporeal gender in the superficial role reversal, and blind to the anti-feminist effects in operation. Critical discourse analysis of an example drawn from the popular US television show American Horror Story illustrates that such depictions operate in discursive space as the locus for a process of ?governmentalized recursion?. A close reading of the media text and its audience reception is performed, methodological considerations in the intersection of feminist analyses and cultural criminology vis a vis gendered lacunae and popular misinterpretation are discussed and the primacy of scenographic analysis is challenged via a focus on ?the arc?. This article thus contributes an intervention in the discourse predicated on a Foucauldian triangulation of media texts, audience responses and institutional frameworks and practices, to comprise a history of the present in a controversial and neglected area.